2023
DOI: 10.1182/bloodadvances.2023009742
|View full text |Cite
|
Sign up to set email alerts
|

Germ line variants in patients with acute myeloid leukemia without a suspicion of hereditary hematologic malignancy syndrome

Abstract: Germline predisposition in acute myeloid leukemia (AML) has gained importance in recent years due to a non-negligible frequency and impact on management of patients and their relatives. Risk alleles for AML development may be present in patients without a clinical suspicion of hereditary hematologic malignancy syndrome. In this study we investigated the presence of germline variants (GV) in 288 genes related to cancer predisposition in 47 patients with available paired tumor-normal material, namely bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Future development of a hematologic tumor testing panel that is also useful in detecting refractory cytopenia and the risk of relapse refractoriness after leukemia-directed therapy is warranted. Extensive sequencing technologies, such as whole exome sequencing (WES), allow for the investigation of new candidate genetic abnormalities, including germline gene variants, at once, and are expected to be utilized more than targeted NGS panels in the future [ 4 , 251 ]. There is a growing need for the expert consultation and clinical surveillance of patients with a germline predisposition to hematologic malignancies [ 252 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future development of a hematologic tumor testing panel that is also useful in detecting refractory cytopenia and the risk of relapse refractoriness after leukemia-directed therapy is warranted. Extensive sequencing technologies, such as whole exome sequencing (WES), allow for the investigation of new candidate genetic abnormalities, including germline gene variants, at once, and are expected to be utilized more than targeted NGS panels in the future [ 4 , 251 ]. There is a growing need for the expert consultation and clinical surveillance of patients with a germline predisposition to hematologic malignancies [ 252 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in some cases of acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS), a hereditary (mainly autosomal dominant) predisposition has been observed [ 2 , 3 ]. Typically, a family in which two or more first- or second-degree relatives have developed acute leukemia (AL), myeloid malignancies, characteristic cytopenias, or either MDS or AML, is defined as “familial MDS/AML”, or, more broadly, hereditary hematologic malignancy syndrome (HHMS) [ 4 , 5 , 6 ]. The field of HHMS has gained increasing recognition among clinicians and scientists worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…However, risk alleles may be present in patients without clinical findings, suggesting hereditary hematologic malignancy syndromes. Guijarro F et al (25) identified pathogenic or likely pathogenic variants in ATM, DDX41, CHEK2, FANCA, FANCM, SBDS, DNAJC21, and CSF3R in 288 acute myeloid patients without criteria that would suggest the presence of hereditary hematologic malignancy syndromes. The existence of de novo or low-penetrance variants, late-onset disease, and incomplete family history contributes to a lack of clinical suspicion (26).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of germline mutations predisposing to an increased risk of myeloid neoplasms is a growing field of interest 1 . A familial or personal history of cancer or pre‐existing cytopenia(s), together with specific clinical findings and an early age of onset of a myelodysplastic syndrome (MDS) or acute myeloid leukemia (AML) are potentially suggestive of an inherited mutation in a gene predisposing to myeloid malignancies, 2 although these risk factors are not always apparent 3 . As a result of this increasing knowledge, the revised 4th edition of the World Health Organization (WHO) classification of hematopoietic and lymphoid tissues published in 2016 recognized myeloid neoplasms with germline predisposition as distinct disease entities 4 .…”
Section: Introductionmentioning
confidence: 99%